Behaviour Recognition with Kinodynamic Planning Over Continuous Domains - Fitzpatrick, Grady; Lipovetzky, Nir; Papasimeon, Michael; Ramirez, Miquel; Vered, Mor (Frontiers in Artificial Intelligence, 2021)
We investigate the application of state-of-the-art goal recognition techniques for behaviour recognition over complex continuous domains using model predictive control (MPC) for trajectory generation. We formally define the problem of kinodynamic behaviour recognition and establish a set of baseline behaviours and performance measures in the complex domain of unmanned aerial maneuvers. We evaluate how well our approach performs over a range of standard aerial maneuvers and representative initial configurations of varying complexity. The work also highlights future research directions in compound model-based behaviour recognition and team behaviour recognition where multiple agents may be acting simultaneously